Size, Growth, Profitability and Capital Structure - Axel Giovanni; Devi Wahyu Utami; Eka Widiyaningrum (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
This study aims to provide empirical evidence regarding the role of profitability, firm size and firm growth in explaining the variability of capital structure. The research sample was taken using purposive sampling method. The research sample that met the criteria was 34 companies in the consumer goods industry which were listed on the Indonesia Stock Exchange for the 2015-2018 period. The independent variables consist of profitability, company size and company growth. In this study, hypothesis testing was carried out using linear regression processed through SPSS software. The coefficient of determination is 98.58%, meaning that the variability of the capital structure is influenced by the variables of profitability, company size and company growth. Based on the results of linear regression analysis with a significance level of 5%, the results provide evidence that there is a negative and significant relationship between profitability and capital structure and there is a positive and significant relationship between company growth and capital structure. This study also provides evidence that firm size has no role as a determinant of capital structure.